Eosinophils: important players in humoral immunity. (28th September 2015) - Berek, C
Summary: Eosinophils perform numerous tasks. They are involved in inflammatory reactions associated with innate immune defence against parasitic infections and are also involved in pathological processes in response to allergens. Recently, however, it has become clear that eosinophils also play crucial non-inflammatory roles in the generation and maintenance of adaptive immune responses. Eosinophils, being a major source of the plasma cell survival factor APRIL (activation and proliferation-induced ligand), are essential not only for the long-term survival of plasma cells in the bone marrow, but also for the maintenance of these cells in the lamina propria which underlies the gut epithelium. At steady state under non-inflammatory conditions eosinophils are resident cells of the gastrointestinal tract, although only few are present in the major organized lymphoid tissue of the gut – the Peyer's patches (PP). Surprisingly, however, lack of eosinophils abolishes efficient class-switching of B cells to immunoglobulin (Ig)A in the germinal centres of PP. Thus, eosinophils are required to generate and to maintain mucosal IgA plasma cells, and as a consequence their absence leads to a marked reduction of IgA both in serum and in the gut-associated lymphoid tissues (GALT). Eosinophils thus have an essential part in long-term humoral immune protection, as they are crucial for the longevity of antibody-producing plasma cells in the bone marrow and, in addition, for gut immune homeostasis.